Identification of CXCL12‐abundant reticular cells in human adult bone marrow. (10th April 2021) - Aoki, Kazunari; Kurashige, Masako; Ichii, Michiko; Higaki, Kei; Sugiyama, Tatsuki; Kaito, Takashi; Ando, Wataru; Sugano, Nobuhiko; Sakai, Takashi; Shibayama, Hirohiko; ,; Takaori‐Kondo, Akifumi; et al.
Summary: A population of mesenchymal stem cells, termed CXC chemokine ligand (CXCL)12‐abundant reticular (CAR) cells or leptin receptor‐expressing cells, are the major cellular component of niches for haematopoietic stem cells (HSCs) in murine bone marrow. CAR cells are characterized by several salient features, including much higher expression of CXCL12, stem cell factor (SCF), forkhead box C1 (FOXC1) and early B‐cell factor 3 (EBF3), which are essential for HSC maintenance, than other cells. However, the human counterpart of CAR cells has not been fully described. Here, we show the presence of cells expressing much higher CXCL12 than other cells in human adult bone marrow using a flow cytometry‐based in situ technique that enables high‐throughput detection of mRNA at single‐cell resolution. Most CXCL12 hi cells expressed high levels of SCF, FOXC1 and EBF3 and had the potential to differentiate into adipocytes and osteoblasts. Histologically, the nuclei of CXCL12 hi cells were identified and quantified by EBF3 expression in fixed marrow sections. CXCL12 hi cells sorted from residual bone marrow aspirates of chronic myeloid leukaemia patients expressed reduced levels of CXCL12, SCF, FOXC1 and EBF3 in correlation with increased leukaemic burden. Together, we identified the human counterpart of CAR cells, enabling the evaluation of their alterations in various haematological disorders by flow cytometric and histological analyses.